THE NATURE OF HUMOR FORMATION IN THE PUBLIC CRITICAL PROGRAM - Laziz Eshonkulov , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The state analyzes the aesthetics of laughter, critically comprehends the foundations of human existence in its tragicomic dimension. The positional role of the philosophy of laughter is revealed through a comparative analysis of philosophical concepts from antiquity to antiquity. Demonstration of tradition and discursive practicality, the characteristic contradiction of the individual and public spirit, the realization of philosophy and laughter, the opposition of possibility and necessity. In general, the philosophy of laughter, from a critical point of view, describes not the tragedy of existence, but the human being of the human being who endlessly overcomes it.